Gestion Des Risques Majeurs Au Maroc: Les Instabilités De Terrain - Yazidi Mohamed; Eloutassi Noureddine; Nabih Khadija; Hammi Abdel Hadi; Yazidi Abdelaziz; Benziane Fouad (European Scientific Journal, ESJ, 2017)
Instabilities of the ground is regarded as one of the most serious problems that affect many areas in Morocco. The study is important and beneficial because it concerns various sections of the Rif area. Indeed, certain zones which came at the top have been seriously affected. Disorders are numerous: destruction of homes, loss of agricultural land, and deterioration of infrastructure (roads, railways, and bridges). The aim of this study is focused on the zones where the road network generally is much damaged. This, however, causes a disturbance and even an interruption of the road traffic during stormy periods. The detailed study of lithology, climatology, geomorphology, hydrology, and the slope of the studied zones allows us to highlight the characteristics of the unstable grounds. It also helped us to figure out that the rheological nature of the ground plays a significant role in the characterization of the type of movement.The analysis of various movements which was found enables us to conclude that an instability of the ground depends on the conjunction on many factors, whether they are of provision or release. The most important factors causing the instabilities of the ground are: The alternation of rocks of nature; permeability and plasticity were well contrasted. The rugged relief and steep slopes. Geotechnical properties. Seismicity. Irregular rainfall. Geomorphology and land use. Anthropogenic action. Spatial distribution of the risk zones shows that the majority of the studied sections experience strong risks and medium risks levels.